Housing Production, City Financiarization and Spatial Ruptures in Latin America: The Case of Bogota - Amezquita, Laura; Vera Büchel, Nelson; Crevoisier, Olivier (My University, 2017)
The article aims to identify how investments operate in real estate sector in Bogota, in particular housing production, so advertise their impact on the urban morphology in terms of residential density. In one hand, we test the disparities in population densities and consequently housing demand, supporting the hypothesis of existence of a heterogeneous and segregated structure. In the other hand, about the city capacity to integrate people, it denotes the inclusion via housing production for low income and low purchase power families, which it has a different logic front of the market to the rest of city population, then they have allocation decisions and integration process to urban circuit developed in a different way. We propose measure the distances to fundamentals urban equipment to examine the constraints that spatial ruptures imposes to inclusion of these population segment. In methodological training we made a cross section exploration using the Multidimensional City Survey for 2014 and official city information to develop a spatial analysis. Ultimately, we expose some final considerations.
Keywords: City financiarisation; Urban Morphology; Bogota